2009
DOI: 10.4314/ajbr.v9i1.48769
|View full text |Cite
|
Sign up to set email alerts
|

Starch based hydrogel with potential biomedical application as artificial skin

Abstract: Hydrogel wound dressing can protect injured skin and keep the wound

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…GA reacts with the hydroxyl groups to form polyacetals. This results in the formation of an interconnecting network structure [55][56][57][58] . b. Glyoxal: Glyoxal is a two-carbon di-aldehyde.…”
Section: Chemical Cross-linkingmentioning
confidence: 99%
“…GA reacts with the hydroxyl groups to form polyacetals. This results in the formation of an interconnecting network structure [55][56][57][58] . b. Glyoxal: Glyoxal is a two-carbon di-aldehyde.…”
Section: Chemical Cross-linkingmentioning
confidence: 99%
“…Biological based dressings are made from biomaterials that play an active part in the wound healing process. They include tissue engineered products derived from natural tissues or artificial sources 15, such as starch 16–21, chitosan 22–25, collagen 26–29, hyaluronic acid 30–33, alginates 34–38, among others.…”
Section: Wound Dressing Productsmentioning
confidence: 99%
“…The development of hydrogels prepared by crosslinking of starch and PVA with glutaraldehyde has been attempted in the past by some researchers. Pal et al 16, 17 reported the preparation of a corn starch‐PVA hydrogel. They used 50 mL of 10% PVA solution and added 50 mL of 5% corn starch.…”
Section: Starch‐based Wound Dressingsmentioning
confidence: 99%
“…Synthetic materials, such as plastics, traditionally convey superiority in addressing the mechanical properties required to support tissue growth and can be easily modified to augment their printability, viscosity, and strength. The major caveat of such materials lies in their restricted bioactivity: limited cell adhesion and lack of extracellular matrix mimicry translate to a limited capacity to support the biological components of cell growth (O'Brien, 2011). Furthermore, synthetic materials are often non-degradable which presents the risks of extrusion, immunogenicity, and impedance of de novo tissue formation (Sarkar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%